National and subnational burden and attributable risk factors of osteoarthritis, rheumatoid arthritis, and low back pain in Iran: 1990–2019 findings of the Global Burden of Disease (GBD) Study - Mahnaz Sanjari; Hossein Yarmohammadi; Sahar Saeedi Moghaddam; Mohammad Amin Habibi; Aida Fallahzadeh; Amir Hossein Behnoush; Shakiba Yousefi; Ali Sheikhy; Sima Noorali; Zahra Esfahani; Narges Ebrahimi; Noushin Fahimfar; et al. (PLoS ONE, 2026)
Background The prevalence of chronic diseases has increased concurrent with the increase in life expectancy and musculoskeletal disorders (MSDs) are among them. They have a high burden all over the world and are among the leading causes of years lived with disability (YLDs). MSDs are generally divided into six categories, and osteoarthritis (OA), rheumatoid arthritis (RA), and low back pain (LBP) are among most of the most prevalent MSDs. In this study, we aimed to assess the burden of these three disorders in Iran. Methods Data were retrieved from the global burden of disease (GBD) study 2019 to investigate the epidemiological features of the burden of RA, OA, and LBP and the attributed burden to their risk factors in Iran and its provinces. Results The total number of OA, RA, and LBP increased from 1990 to 2019. Although the age-standardized incidence rate (ASIR) of LBP decreased by −8.4%, the ASIR of OA and RA increased by 7.3% and 7.6% (reached 445.0 (95% uncertainty interval 395.9 to 501.9) and 5.0 (4.5 to 5.6) per 100,000 population in 2019, respectively). The age-standardized prevalence rate (ASPR) of OA and RA increased by 7.0% and 9.3%, respectively (5588.2 (5041.2 to 6228.6) and 109.1 (97.8 to 120.9) in 2019) while, the ASPR of LBP decreased by 9.5% (8,486.5 (7,533.8 to 9,528.3) in 2019). Females were more prone to establish OA and RA, but males were more predisposed to developing LBP. The highest OA incidence rate was presented in 55–59 years with a decreasing pattern over 59 years, 35–39 years with a decreasing pattern for older patients for RA, and 75–79 years with an increasing LBP incidence observed as age increased. Conclusion LBP, OA, and RA are still significant health issues, and the number of patients is increasing, which imposes much burden. The increase in the prevalence of MSDs in Iran alarmingly highlights the need for immediate policies designed to reduce their burden. Therefore, epidemiological information helps make policies and reallocate sources that can improve healthcare services.